The Portraits of Minahasan Women: Empowerment and Challenges - Rorintulus, Olga A.; Wuntu, Ceisy N.; Mangundap, Juniva J.; Lumi, Elsinta C. (Journal of English Culture, Language, Literature and Education, 2023)
The Minahasan community of North Sulawesi, Indonesia has witnessed a significant shift in women's roles and empowerment in recent years. This study examined the economic and social/political empowerment of Minahasan women, including their participation in income-generating activities, entrepreneurship, community leadership, and advocacy for rights and representation. However, this empowerment has also brought about challenges as Minahasan women grapple with the double burden of balancing their newly acquired roles with traditional domestic responsibilities of childcare and household duties. Through a comprehensive library research approach, this study analyzed the tensions and role conflicts experienced by Minahasan women as they navigated the contrasting societal expectations. Key findings revealed the strain on family dynamics, potential neglect of children's upbringing, and marital relationship challenges arising from the double burden. The study also identified strategies and best practices for reconciling these contrasting roles, such as promoting equitable domestic workload sharing, establishing childcare support systems, advocating for flexible work arrangements, and fostering societal attitude changes towards gender norms. Ultimately, this research highlights the importance of addressing the double burden challenges faced by Minahasan women to ensure their empowerment is sustainable and does not come at the cost of sacrificing traditional caregiving responsibilities or family well-being.